Newfoundland and Labrador : a history - Cadigan, Sean T. (Sean Thomas), 1962- (Buffalo : University of Toronto Press, 2009)
"Published to coincide with the sixtieth anniversary of Newfoundland and Labrador joining Canada, Sean T. Cadigan has written the book that will surely become the definitive history of one of North America's most distinct and beautiful regions. The site of the first European settlement by Vikings one thousand years ago, a former colony of England, and known at various times as Terra Nova and Newfoundland until its official name change to Newfoundland and Labrador in 2001, this easternmost point of the continent has had a fascinating history in part because of its long-held position as the gateway between North America and Europe. Examining the region from prehistoric times to the present, Newfoundland and Labrador is not only a comprehensive history of the province, but an illuminating portrait of the Atlantic world and European colonisation of the Americas.